2001
DOI: 10.1139/z01-134
|View full text |Cite
|
Sign up to set email alerts
|

Influence of breeding habitat on bear predation and age at maturity and sexual dimorphism of sockeye salmon populations

Abstract: Age structure and morphology differ among Pacific salmon (Oncorhynchus spp.) populations. Sexual selection and reproductive capacity (fecundity and egg size) generally favor large (old), deep-bodied fish. We hypothesized that natural selection from physical access to spawning grounds and size-biased predation by bears, Ursus spp., opposes such large, deep-bodied salmon. Accordingly, size and shape of salmon should vary predictably among spawning habitats. We tested this hypothesis by measuring the age composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
158
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(165 citation statements)
references
References 48 publications
7
158
0
Order By: Relevance
“…We found similar patterns of phenotypic divergence (deeper bodies and larger eggs among beach than tributary spawners) among Lake Clark sockeye salmon as in other lake systems (Blair et al 1993;Quinn et al 1995Quinn et al , 2001Hendry et al 2000b). This parallel pattern of divergence cannot be due to random genetic drift and provides indirect evidence that such differences are adaptive.…”
Section: Beach and Tributary Habitatssupporting
confidence: 70%
See 1 more Smart Citation
“…We found similar patterns of phenotypic divergence (deeper bodies and larger eggs among beach than tributary spawners) among Lake Clark sockeye salmon as in other lake systems (Blair et al 1993;Quinn et al 1995Quinn et al , 2001Hendry et al 2000b). This parallel pattern of divergence cannot be due to random genetic drift and provides indirect evidence that such differences are adaptive.…”
Section: Beach and Tributary Habitatssupporting
confidence: 70%
“…Parallel patterns of phenotypic divergence between fish spawning in beach and tributary habitats among nursery lakes has prompted definition of spawning ecotypes of sockeye salmon. For example, the beach spawning ecotype is characterized by larger eggs, deeper bodies, smaller size at age, younger age at maturity, and later spawning times than the inlet tributary ecotype (Blair et al 1993;Quinn et al 1995Quinn et al , 2001Wood 1995;Hendry et al 2000b).…”
Section: Introductionmentioning
confidence: 99%
“…However, size-selective predation by bears (16)(17)(18) and physical access to shallow streams (18,19) favor smaller fish in the evolution of body size and morphology. The result is that salmon spawning on mainland and island beaches, where there is little predation and no difficulty of access, are deep-bodied for their length compared with sockeye spawning in rivers and creeks (19). In addition, the average age at maturity is greater for sockeye spawning in larger rivers than in smaller creeks (19,20).…”
Section: The Biodiversity Of Bristol Bay Sockeyementioning
confidence: 99%
“…The result is that salmon spawning on mainland and island beaches, where there is little predation and no difficulty of access, are deep-bodied for their length compared with sockeye spawning in rivers and creeks (19). In addition, the average age at maturity is greater for sockeye spawning in larger rivers than in smaller creeks (19,20).…”
Section: The Biodiversity Of Bristol Bay Sockeyementioning
confidence: 99%
“…In many watersheds, differentiation is present among nursery lakes and populations spawning in different habitats within each lake (Wood 1995;Seeb et al 2000;Habicht et al 2007;Gomez-Uchida et al 2011). Age at maturity, adult body size and shape (Quinn et al 2001;Carlson et al 2009), and spawn timing often vary among populations. Studies of different spawning types have shown that body size can be limited by water depth at the spawning grounds (Quinn et al 2001;Ramstad et al 2010) and that variation in flow and predation pressure can drive phenotypic divergence (Hendry et al 2000;Carlson et al 2009).…”
mentioning
confidence: 99%